Patients with fever of unknown origin (FUO): diagnosis by nuclear medicine imaging - Meiler, J.; Becker, W. (Nuklearmedizin - NuclearMedicine, 2001)
Fever of unknown origin (FUO) in immunocompetent and non neutropenic patients is defined as recurrent fever of 38,3° C or greater, lasting 2-3 weeks or longer, and undiagnosed after 1 week of appropriate evaluation. The underlying diseases of FUO are numerous and infection accounts for only 20-40% of them. The majority of FUO-patients have autoimmunity and collagen vascular disease and neoplasm, which are responsible for about 50-60% of all cases. In this respect FOU in its classical definition is clearly separated from postoperative and neutropenic fever where inflammation and infection are more common. Although methods that use in-vitro or in-vivo labeled white blood cells (WBCs) have a high diagnostic accuracy in the detection and exclusion of granulocytic pathology, they are only of limited value in FUO-patients in establishing the final diagnosis due to the low prevalence of purulent processes in this collective. WBCs are more suited in evaluation of the focus in occult sepsis. Ga-67 citrate is the only commercially available gamma emitter which images acute, chronic, granulomatous and autoimmune inflammation and also various malignant diseases. Therefore Ga-67 citrate is currently considered to be the tracer of choice in the diagnostic work-up of FUO. The number of Ga-67-scans contributing to the final diagnosis was found to be higher outside Germany than it has been reported for labeled WBCs. F-l 8-2’-deoxy-2-fluoro-D-glucose (FDG) has been used extensively for tumor imaging with PET. Inflammatory processes accumulate the tracer by similar mechanisms. First results of FDG imaging demonstrated, that FDG may be superior to other nuclear medicine imaging modalities which may be explained by the preferable tracer kinetics of the small F-l 8-FDG molecule and by a better spatial resolution of coincidence imaging in comparison to a conventional gamma camera.
Keywords: Fever of unknown origin; FUO; scintigraphy; PET